Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Show that there is a unique solution of the differential equation $tx'(t)=(2t^2+1)x(t)+t^2,t>0$, which has a finite limit as $t\rightarrow \infty$ and compute this limit.

share|cite|improve this question

Rewrite $$ tx' - (2t^2 + 1)x = t^2 $$ Multiply through by integration factor, $\mu(t)$, and divide by $t$: $$ \mu x' - (2t + 1/t)\mu x = t\mu \;\;\;\;\;(1)$$

Define $\mu(t)$ such that: $-(2t+1/t)\mu = \mu'$ (2).

Plugging (2) into (1) we get: $$ \mu x' + \mu' x = t\mu$$ Reverse the product rule: $$ \frac{d}{dt} (\mu x) = t\mu$$

Thus, $\mu x = \int t\mu dt$ and finally: $$ x(t) = \frac{\int t\mu(t) dt}{\mu(t)} \;\;\;\;\;\;\;(3) $$

From (2) we see that $-(2t + 1/t) = \mu'/\mu = d/dt\ln(\mu)$ and thus: $$ \ln(\mu) = \int -(2t + 1/t) \;dt = -t^2 - \ln(t) + C $$ Solve for $\mu(t)$: $$ \mu(t) = e^{-t^2 - \ln(t) + C} = Ce^{-t^2}/t \;\;\;\;\;(4)$$

Plug (4) into (3): $$ x(t) = \frac{\int t Ce^{-t^2}/t \;dt}{Ce^{-t^2}/t} = \frac{\int e^{-t^2} \;dt}{e^{-t^2}/t}$$

The right hand integral has no closed-form algebraic expression. This is solved, essentially, for $x(t)$. We could use the error function, if you wish: $$ x(t) = \frac{\frac{1}{2}t\sqrt{\pi}\;\mathrm{erf}(t) + Ct}{e^{-t^2}}$$

share|cite|improve this answer
There are many solutions, of the form $te^{t^2} \{A + \int_{-\infty}^t e^{-s^2} \,ds\}$. Choosing the constant appropriately, by observing that $\lim_{t\to\infty} \int_{-\infty}^t e^{-s^2}\,ds$ is finite, fixes the desired solution and lets one compute the limit. – Eugene Shvarts Feb 11 '13 at 8:04

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.